2012
DOI: 10.1016/j.mcn.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcript expression levels of full-length alpha-synuclein and its three alternatively spliced variants in Parkinson's disease brain regions and in a transgenic mouse model of alpha-synuclein overexpression

Abstract: Alternative splicing is a complex post-transcriptional process that can be regulated by cis-acting elements located within genomic non-coding regions. Recent studies have identified that polymorphic variations in non-coding regions of the α-synuclein gene (SNCA) locus are associated with an increased risk for developing Parkinson’s disease (PD). The underlying mechanism(s) for this susceptibility may involve changes in α-synuclein mRNA expression and alternative splicing. As a first step towards understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…As expected, human ␣-synuclein is expressed at elevated levels in both ASOTg SN and Cyt fractions (Rockenstein et al, 2002;Watson et al, 2009). Human ␣-synuclein's expression is similar in both the ASOTg SN and Cyt fraction, but a minor amount of a truncated ␣-synuclein isoform of ∼10-12 kDa size is also evident in the ASOTg SN, possibly due to carboxyl terminal cleavage (Li et al, 2005) and/or alternative RNA splicing (McLean et al, 2012).…”
Section: Mouse Forebrain Snssupporting
confidence: 71%
“…As expected, human ␣-synuclein is expressed at elevated levels in both ASOTg SN and Cyt fractions (Rockenstein et al, 2002;Watson et al, 2009). Human ␣-synuclein's expression is similar in both the ASOTg SN and Cyt fraction, but a minor amount of a truncated ␣-synuclein isoform of ∼10-12 kDa size is also evident in the ASOTg SN, possibly due to carboxyl terminal cleavage (Li et al, 2005) and/or alternative RNA splicing (McLean et al, 2012).…”
Section: Mouse Forebrain Snssupporting
confidence: 71%
“…For example, Alzheimer disease and LB dementia brains seem to be characterized by higher ␣-syn-98 mRNA levels (106) and lower ␣-syn-126 expression (107), whereas an increased level of ␣-syn-112 was reported to be specific for LB dementia patients (108). A recent study suggested a global trend for increased expression of the four ␣-syn splicing variant mRNAs between control and PD patients, but the expression levels were found to vary between different brain regions (109). Surprisingly, clinical studies of ␣-syn isoforms have so far relied only on mRNA analysis, mainly because the levels of expression of the corresponding proteins are very low.…”
mentioning
confidence: 99%
“…PD-associated mitochondrial dysfunction induces α-syn [ 71 , 118 , 119 ], which may represent a retrograde signal designed to dampen the bioenergetic burden of synaptic transmission by blocking vesicle exocytosis and neurotransmitter release [ 120 ], to preserve neuronal Ca 2+ homeostasis at MAMs [ 117 ], or to decrease oxidative stress associated with dopamine autoxidation [ 116 ] within the PD brain [ 119 ].…”
Section: α-Synuclein To Lewy Bodiesmentioning
confidence: 99%